2007
DOI: 10.1002/dvdy.21398
|View full text |Cite
|
Sign up to set email alerts
|

HB‐EGF decelerates cell proliferation synergistically with TGFα in perinatal distal lung development

Abstract: Heparin-binding epidermal growth factor-like growth factor (HB-EGF) is a member of the EGF family of growth factors that is suggested to be involved in distal lung development. In HB-EGF null (HB del/del ) newborns, a histopathologic analysis revealed abnormally thick saccular walls occurring from embryonic day 18.5 that reduced the terminal saccular space area. HB-EGF gene deletion resulted in a significant increase in cell proliferation, indicating that HB-EGF suppresses distal lung cell proliferation. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…TGF-␣ is a known stimulant of angiogenesis and alveolar epithelial differentiation. Pulmonary overexpression of TGF-␣ disrupts lung morphology in mice (14), while paradoxically TGF-␣ knockout also results in a reduction of the terminal gas exchange area (26). The latter corresponds to our findings of reduced TGF-␣ being associated with the development of BPD.…”
Section: Discussionsupporting
confidence: 88%
“…TGF-␣ is a known stimulant of angiogenesis and alveolar epithelial differentiation. Pulmonary overexpression of TGF-␣ disrupts lung morphology in mice (14), while paradoxically TGF-␣ knockout also results in a reduction of the terminal gas exchange area (26). The latter corresponds to our findings of reduced TGF-␣ being associated with the development of BPD.…”
Section: Discussionsupporting
confidence: 88%
“…These results are in part consistent with our finding that HB hb/hb valves had a slightly, but significantly, increased number of endocardial cells compared with WT valves at E17.5 (Fig. 4C) Interestingly, although Hbegf-null mice show severe defects in heart chamber formation and distal lung development Minami et al, 2008), we found that HB hb/hb mice did not exhibit these abnormalities (see Fig. S5H,I in the supplementary material).…”
Section: Truncating the Heparin-binding Domain Of Hb-egf Causes Cardisupporting
confidence: 91%
“…These findings suggest that the HB-EGF-HSPG interaction is not essential for cardiac muscle homeostasis, and that when HB-EGF is defective in its interaction with HSPGs, this does not affect HB-EGF signaling in this process. Hbegf-null mice also have abnormal perinatal distal lung development Minami et al, 2008). However, we could not detect any abnormalities in HB hb/hb lung development (see Fig.…”
Section: Research Articlementioning
confidence: 59%
See 2 more Smart Citations